Optimal joint production and green investment decisions of green credit financing under uncertain demands - Zhiping Yu; Xin Feng (Frontiers in Environmental Science)
Green credit financing (GCF) is a specialized financial service offered by banks, aimed at incentivizing borrowers to engage in environmentally sustainable investments, and thus promote sustainable development. It is worth noting that in the practical economic environment, the ability of enterprises to adapt their production and green investment decisions to unforeseen market demand is critical for their green credit financing. This paper investigates a joint production and green investment optimization problem of manufacturers financed through GCF under uncertain demand. Only the interval bound of the demand are known. The problem is initially formulated as a min-max regret model to maximize robustness. Based on problem characterizations, an optimal joint production and green investment decision is proposed. To determine the effectiveness of the proposed decision, computational experiments are conducted on real-world instances. Besides, sensitivity analysis is conducted to derive managerial insights on the implementation of GCF under uncertain demand.